Current prevalence of rotator cuff tear in Type 2 diabetes mellitus patients and its association with type of diabetic drug regime (OHA’S vs. insulin therapy) – A prospective study - Arivoli Subramanian,; Vijayashankar Murugesan,; Prem Kumar Kothimbakkam,; Bharath Vadivel Kumar, (Asian Journal of Medical Sciences, 2024)
Background: A prospective study to assess the prevalence of rotator cuff (RC) tears in patients with Type 2 diabetes mellitus. Aims and Objectives: The purpose of this study is to assess the prevalence of RC tear in Type 2 diabetes mellitus patients presenting with shoulder pain to the outpatient clinic. Materials and Methods: A total of 100 diabetic patients with shoulder pain and restriction of movements formed the study group and were prospectively studied using magnetic resonance imaging and were evaluated with regard to the presence of RC tear. The factors that were analyzed included HBA1C levels, duration of diabetes, and type of diabetic medication. All these factors were evaluated with regard to their correlation with RC tear. Results: In our study, we found that the prevalence of RC tear was 37% and there seemed to be a significant correlation between HBA1C levels (P=0.007) as well as prolonged duration of diabetes (P=0.006) with RC tear. It has been established in our study that the occurrence of RC tear is lesser in oral hypoglycemic agents group as compared to insulin group in treating diabetic patients. Conclusion: One independent risk factor for RC tear is diabetes. The prevalence of RC tear is higher in the diabetic population with increased HBA1c levels and prolonged duration of diabetes mellitus. Metformin usage in diabetes mellitus has been associated with reduced incidence of RC tear due to diminished impregnation of advanced glycation end products with in the RC tendon.